Re-thinking SoTL for the Age of GenAI: Diffracted, Entangled, and Human - Mills, Jennie; Beynen, Tina; Chia Sook May, Ivy; Fitzgerald, Rachel; Hall, Kimberly A.; Lai, Evelyn; Mason, Jon; Newell, Samantha (Teaching and Learning Inquiry, 2025)
The rapid advancement of generative artificial intelligence (GenAI) necessitates a re-evaluation of established Scholarship of Teaching and Learning (SoTL) frameworks. This paper presents a novel approach to pedagogical research through the lens of diffraction, enabling educators to embrace uncertainty, build trust with technology, and reconceptualize practices within a GenAI-led education landscape. We offer five key propositions, each paired with prompts to support collaborative exploration of GenAI. These propositions advocate for a multidisciplinary and context-aware methodology that moves beyond traditional SoTL perspectives and reflective practice. Framing GenAI as both a challenge and an opportunity, we call for a reimagining of SoTL as a dynamic, inclusive and entangled field capable of addressing the complexities of AI-enhanced learning environments. The diffractive approach foregrounds human and non-human entanglement, creating transformative pedagogical practices. Designed as a practical and theoretical guide, our propositions and prompts offer SoTL scholars new ways to engage with GenAI through posthuman, critically informed lenses.